Landmark essays on american public address - Medhurst, Martin J. (Routledge, Taylor & Francis Group, 2010)
This volume traces the historical evolution of American academic thought concerning public address -- what it is, how it ought to be studied, and what can be learned by engaging rhetorical texts in an analytical fashion. To begin, one must distinguish among three separate but interrelated uses of the term "public address" -- as practice, theory, and criticism. The essays in this volume represent landmarks in the literal sense of that term -- they are marks on the intellectual landscape that indicate where scholars and ideas have passed, and in that passing left a mark for future generations. It is appropriate to revisit the landmarks that have set public address off as a field of study and it allows readers to remember the struggles that have led to the current situation. Most of the authors of the following chapters are deceased, but their ideas live on -- transformed, adapted, modified, rejected, and reborn. The scholarly dialectic continues. What constitutes a study in public address, how best to approach rhetorical texts, which analytical tools are required for the job, how best to balance text with context and what role ought theory to play in the conduct or outcome of critical inquiry -- these questions live on. To answer them at all is to engender debate and that is how it should be if the intellectual vitality of public address is to be maintained. The papers are a prolegomenon to such studies, for they mark where scholars have been and point the way to where they still must go.